2014
DOI: 10.1186/s12888-014-0219-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cost effectiveness of staff training in Positive Behaviour Support (PBS) for treating challenging behaviour in adults with intellectual disability: a cluster randomised controlled trial

Abstract: BackgroundMany people with intellectual disability present with challenging behaviour which often has serious consequences such as the prescription of long term medication, in-patient admissions and disruption of normal daily activities. Small scale studies of Positive Behaviour Support (PBS) delivered by paid carers suggest that it reduces challenging behaviour and costs of care and improves quality of life. This study aims to investigate whether professionals training in the delivery of PBS as part of routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…An RCT currently in progress, evaluating the clinical and cost effectiveness of training staff in PBS versus usual care will also help to improve the evidence base further. The trial aims to recruit 246 adults to the trial with 12-months follow-up (Hassiotis et al 2014). In addition to providing information on a mechanism for implementing PBS in services it presents an opportunity to increase the evidence for the cost of challenging behaviour in learning disabilities.…”
Section: Future Researchmentioning
confidence: 99%
“…An RCT currently in progress, evaluating the clinical and cost effectiveness of training staff in PBS versus usual care will also help to improve the evidence base further. The trial aims to recruit 246 adults to the trial with 12-months follow-up (Hassiotis et al 2014). In addition to providing information on a mechanism for implementing PBS in services it presents an opportunity to increase the evidence for the cost of challenging behaviour in learning disabilities.…”
Section: Future Researchmentioning
confidence: 99%
“…5 Challenging behavior is associated with increases in receipt of antipsychotic medication, service use, hospitalization, restrictive care practices, and deprivation. 6 In relation to potential contributors to challenging behavior in individuals with epilepsy, comorbid psychopathology was associated with violence in a meta-analysis of violence in epilepsy. 7 However, few studies examine reported incidents of challenging behavior in epilepsy or factors associated with such incidents.…”
mentioning
confidence: 99%
“…The overall median level of challenging behaviour of the participants was higher than that reported in a trial of antipsychotic medication by Tyrer et al 61 In order to guard against the tendency for the impact of training to dissipate over time, we set up mentoring and peer support during the study period. 1,28,93 Our process evaluation indicated that training in PBS was well received by the therapists and the delivery of PBS was welcome and highly valued by the service managers of participating services, carers and participants with ID.…”
Section: Strengths and Limitationsmentioning
confidence: 99%